2011
DOI: 10.1017/s0950268810003006
|View full text |Cite
|
Sign up to set email alerts
|

Facemasks and intensified hand hygiene in a German household trial during the 2009/2010 influenza A(H1N1) pandemic: adherence and tolerability in children and adults

Abstract: SUMMARYNon-pharmaceutical interventions (NPI) such as facemasks and intensified hand hygiene may be effective in preventing influenza infections in households. It may be equally important that household members, especially children, can learn to use, maintain and tolerate these measures. We monitored adherence and tolerability of these NPI within a cluster-randomized trial in households with influenza index patients. We recruited 147 participants in 41 households, 39 (95 %) out of 41 index patients were childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 13 publications
1
34
0
2
Order By: Relevance
“…[37][38][39] In contrast, RCTs have not shown the effectiveness of hand hygiene to prevent household transmission of ARIs, regardless of etiology. [40][41][42] However, another randomized controlled trials found no effectiveness of handwashing in influenza prevention, even with masking. [40][41][42] However, another randomized controlled trials found no effectiveness of handwashing in influenza prevention, even with masking.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] In contrast, RCTs have not shown the effectiveness of hand hygiene to prevent household transmission of ARIs, regardless of etiology. [40][41][42] However, another randomized controlled trials found no effectiveness of handwashing in influenza prevention, even with masking. [40][41][42] However, another randomized controlled trials found no effectiveness of handwashing in influenza prevention, even with masking.…”
Section: Discussionmentioning
confidence: 99%
“…Although, at least in theory, compliance with influenza prevention measures should be quite simple, 36–39 the acceptability of these measures among travellers was unknown. To our knowledge, our study is the first to evaluate the associations between determinants of intention by travellers to comply with antiviral recommendations and individual cognitive factors.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed ten studies of hand hygiene and facemask use in developed countries, and obtained an insignificant estimate of risk reduction associated with hand hygiene alone (RR: 0.82; 95% CI 0.66–1.02) but a significant risk reduction when hand hygiene was practiced in conjunction with facemask use (RR: 0.73; 95% CI 0.53–0.99). However, only one of these ten studies [51] was performed in a pandemic setting, with the other nine dealing instead with seasonal influenza control. With small sample size limiting generalizability (n = 149), insignificant risk reductions associated with hand hygiene and facemask use for laboratory-confirmed influenza (RR: 0.64; 95% CI 0.32–1.29) and influenza-like illness (RR: 0.52; 95% CI 0.21–1.29) were found in the pandemic study [51].…”
Section: Resultsmentioning
confidence: 99%
“…However, only one of these ten studies [51] was performed in a pandemic setting, with the other nine dealing instead with seasonal influenza control. With small sample size limiting generalizability (n = 149), insignificant risk reductions associated with hand hygiene and facemask use for laboratory-confirmed influenza (RR: 0.64; 95% CI 0.32–1.29) and influenza-like illness (RR: 0.52; 95% CI 0.21–1.29) were found in the pandemic study [51]. Mukerji et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation